The function of psychotherapy in the interaction between services and territory: How to translate the requests of territories to plan interventions - Sarubbo, Maria (Quaderni di Psicologia Clinica, 2015)
This paper offers a specific contribution on the function of psychotherapy in the maintenance of the interaction between services and territories. Territorialization is a way to organize service delivery. The term territory not only refers to a geographical area but, also, to a common, shared context where social dynamics, problems and intervention requests take shape and meaning. If, on the one hand, services are characterized by the offer of professional performances matching their representation of intervention requests, on the other one, territories organize requests according to their representation of services. Psychotherapy promotes critical thinking in the relastionship of supply and demand through a dialogue between what is historically established by the social mandate of services and the result of the analysis of requests in consideration of their historical and social mutability. The paper discusses a request for a psychotherapy in relation to an eating disorder.